Solve for m 660m=km

Math
660m=km
Subtract km from both sides of the equation.
660m-km=0
Factor m out of 660m-km.
Tap for more steps…
Factor m out of 660m.
m⋅660-km=0
Factor m out of -km.
m⋅660+m(-k)=0
Factor m out of m⋅660+m(-k).
m(660-k)=0
m(660-k)=0
Divide each term by 660-k and simplify.
Tap for more steps…
Divide each term in m(660-k)=0 by 660-k.
m(660-k)660-k=0660-k
Cancel the common factor of 660-k.
Tap for more steps…
Cancel the common factor.
m(660-k)660-k=0660-k
Divide m by 1.
m=0660-k
m=0660-k
Divide 0 by 660-k.
m=0
m=0
Solve for m 660m=km

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top